Entacapone polymorphs: crystal structures, dissolution, permeability, and stability - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Rai, Sunil K.; Suresh, Kuthuru; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
Entacapone (ETP) is a catechol-O-methyltransferase (COMT) drug used to treat Parkinson's disease. ETP is available in the marketplace under the brand name Comtan since 2010, and ETP form-I was first reported in a patent published in 2001. However, analysis of its Xray crystal structures and stability relationship of ETP polymorphs and their dissolution and permeability profile have not yet been reported. We crystallized two new conformational polymorphs of ETP from a water and acetone mixture and studied the structural origin of polymorphism and their phase transformations, stability, equilibrium solubility, dissolution, and permeability properties. The ETP molecule adopts different conformations in the polymorphic structures with slight changes in carbonyl and nitrile group orientations. Thermal analysis suggests that form-III and form-IV are enantiotropically related to form-I, which is the thermodynamically stable form at ambient conditions. In contrast, form-II is monotropically related to form-I. Equilibrium solubility, dissolution, and permeability studies show that form-II persists in the slurry medium and dissolves faster with a high flux rate compared to the stable form-I in phosphate buffer solution at 37 +/- 0.5 degrees C.